A Multidisciplinary Design Education Facing Climate Change (EAAE Annual Conference Proceedings, 2023)
To deal with global challenges we face such as climate change, the New European Bauhaus vision depends on educated and empowered citizens. According to this initiative, architecture and urban planning are only effective when a multidisciplinary approach is applied. This is even more important when integrating sustainability into design education and research.